PERAN TV DIGITAL SEBAGAI MEDIA LITERASI BUDAYA DAN KARAKTER SISWA - Ristin Muhoramah; Wardah Salwa Aqilah; Nur Fadillah Busran; Abdul Azis Khori (CV. ADIBA AISHA AMIRA (ADISAM PUBLISHER), 2026)
This study examines the role of digital television as a medium for cultural literacy and student character development in Indonesia using a qualitative Systematic Literature Review (SLR) of publications from 2021–2024. Relevant studies were retrieved from national and international databases (e.g., Google Scholar, ERIC, ScienceDirect, SINTA/Portal Garuda) using keywords related to digital television, cultural literacy, character education, and media literacy, and were synthesized through thematic content analysis to identify patterns, trends, and research gaps. The findings indicate that digital television has strong potential to enhance students’ cultural literacy when it offers authentic local-culture content that is relevant to students’ everyday lives and packaged with high-quality audio-visual features and interactive formats aligned with the preferences of digital natives. In terms of character education, educational programs that embed values such as honesty, responsibility, tolerance, and cooperation are more effective when they include positive role models, contextual moral dilemmas, and consistent exposure supported by mediation from teachers and parents. However, the educational potential of digital television remains constrained by the dominance of commercially driven entertainment content, uneven production quality and cultural accuracy, and limited integration of media literacy into instructional practice. This study recommends strengthening broadcasting regulations and incentives for educational and cultural programming, fostering collaboration among broadcasters, educators, and cultural experts, and integrating digital TV content into classroom and home learning alongside structured media literacy activities to maximize its contribution to cultural understanding and character formation.